Novel back‐channel‐etch process flow based a‐IGZO TFTs for circuit and display applications on PEN foil. Issue 9 (12th November 2013) - Nag, Manoj; Rockele, Maarten; Steudel, Soeren; Chasin, Adrian; Myny, Kris; Bhoolokam, Ajay; Willegems, Myriam; Smout, Steve; Vicca, Peter; Ameys, Marc; Ke, Tung Huei; Schols, Sarah; et al.
Abstract In this study, we report high‐quality amorphous indium–gallium–zinc‐oxide (a‐IGZO) thin‐film transistors (TFTs) fabricated on a polyethylene naphthalate foil using a new back‐channel‐etch (BCE) process flow. The BCE flow allows a better scalability of TFTs for high‐resolution backplanes and related circuits. The maximum processing temperature was limited to less than 165 °C in order to ensure good overlay accuracy (<1 µm) on foil. The presented process flow differs from the previously reported flow as we define the Mo source and drain contacts by dry etch prior to a‐IGZO patterning. The TFTs show good electrical performance, including field‐effect mobilities in the range of 15.0 cm2/(V·s), subthreshold slopes of 0.3 V/decade, and off‐currents <1.0 pA on foil. The threshold voltage shifts of the TFTs measured were less than 1.0 V after a stressing time of 104 s in both positive (+1.0 MV/cm) and negative (−1.0 MV/cm) bias directions. The applicability of this new BCE process flow is demonstrated in a 19‐stage ring oscillator, demonstrated to operate at a supply voltage of 10 V with a stage delay time of 1.35 µs, and in a TFT backplane driving a 32 × 32 active‐matrix organic light‐emitting diode display.